A one-hour walk in nature reduces amygdala activity in women, but not in men - Sudimac, Sonja; Kühn, Simone (Frontiers in Psychology, 2022)
Urban dwellers are more likely to develop mental disorders such as mood and anxiety disorder as well as schizophrenia compared to rural dwellers. Moreover, it has been demonstrated that even short-term exposure to nature can improve mood and decrease stress, but the underlying neural mechanisms are currently under investigation. In the present intervention study, we examined the effects of a one-hour walk in an urban vs. natural environment on activity in the amygdala, a brain region previously associated with stress processing. Before and after the walk 63 participants underwent an fMRI paradigm inducing social stress. Since there is a pronounced gap in the literature regarding interindividual differences in stress-related neural effects of urban and natural environments, we set out to explore sex differences. We observed that amygdala activity decreased after the walk in nature, but only in women, suggesting that women may profit more from salutogenic effects of nature. Moreover, performance on the arithmetic tasks improved in women after the walk in nature, whereas men performed better after the walk in the urban environment. Few studies report differential tendencies in men and women concerning the stress-related neural effects of acute exposure to an urban vs. natural environments. Furthermore, our findings highlight the importance of sex differences when exploring effects of the environment on brain function and stress Evidence for beneficial effects of nature on stress-related brain regions may inform urban design policies to focus on providing more accessible green areas in cities and this study suggests that sex differences in experiencing the environment should be taken into consideration.